Khs-Warrior Program: Improving Students Awareness and Concern In Nagari Singgalang As the Future Generation for Sustainable Conservation Of The Rare And Endemic Sumatran Rabbit (Nesolagus netscheri) - Satria, Rijal (Fakultas MIPA Universitas Negeri Padang, 2025)
Development and construction have neglected the balance of nature. This community service program aims to educate students in Nagari Singgalang, located around the Singgalang Tandikek Nature Tourism Park, through biodiversity education. This program targets school students, providing knowledge about endemic and protected species, especially the Sumatran striped rabbit (Nesolagus netscheri). This activity is also carried out using a more fun method to make it easier for students to understand. Activities include material delivery, coloring activities, making sculptures, and also face painting. Evaluation using pre-tests and post-tests showed an increase in participants' photography knowledge (the average score from initially low to increased, which indicates an increase in awareness and skills in documenting biodiversity. This program successfully raised students' awareness of the importance of their role in protecting the biodiversity around them